HUBUNGAN PENYESUAIAN DIRI, DUKUNGAN SOSIAL TEMAN SEBAYA DAN SELF REGULATION TERHADAP MOTIVASI BELAJAR SISWA KELAS AKSELERASI SMP NEGERI 1 PALU - Fatimah Saguni; Sagir M. Amin (ISTIQRA, 2014)
This research aimed to explore the relationship adjustment with the motivation to learn, social support peer learning motivation, and self regulation with student motivation on accelerated classes of SMPN 1. Data collected were analyzed using statistical method. Research showed, the first hypothesis was not obtained significant negative correlation between conformity with the motivation to learn or rxy of -0.332 with p> 0.05 (p = 0.142). The magnitude of the coefficient of determination (R2) of 0.076. The second hypothesis was not obtained significant positive correlation between peer support and motivation to learn or rxy of 0.044 with p> 0.05 (p = 0.851). The magnitude of the coefficient of determination (R2) of 0.008. This means that the variable peer support a contribution of 0.8% of the students' motivation accelerated classes SMPN1 Palu. The third hypothesis was obtained significant positive correlation between self-regulation and motivation to learn or rxy of 0.322 with p> 0.05 (p = 0.155). The magnitude of the coefficient of determination (R2) of 0.070. This means that self-regulation variables contributed 7.0% of the students' motivation accelerated classes SMPN1 Palu